Pengaruh Terapi Cermin (Mirror Therapy) Terhadap Adaptasi Fisik Pada Pasien Pasca Stroke - Laili, Nurul (PENA NURSING, 2024)
Post-stroke patients often experience disturbances in movement function due to paralysis, either partial or total paralysis. One of the solutions to help post-stroke patients train their range of motion is by administering mirror therapy. This study was conducted at the Prambon Health Center to examine the impact of mirror therapy on post-stroke patients' ability to adjust physically. The IPAQ (International Physical Activity Questionnaire) was employed as a measuring tool as part of this study's pre-experimental, one group, pre-posttest design approach. The study's population consisted of 21 respondents, and using a total sampling technique, 21 respondents were selected as the sample. Data were analyzed by Paired t-test. The results showed that before the intervention was given most of the respondents (66.7%) had moderate physical activity criteria and after the intervention was given most of the respondents (85.7%) had moderate physical activity criteria. The results of the analysis showed that the p value of 0.000 means that there is an effect of mirror therapy on physical adaptation in post-stroke patients. Mirror therapy can affect physical adaptation by providing visual stimulation to the brain through observing healthy body parts through mirror reflections. The main key to the success of the mirror therapy intervention is that it occurs when the respondent is serious and focused in carrying out each stage of this intervention. Respondents are expected to apply this intervention as often as possible so that the range of motion can be honed properly and physical adaptation can increase.